Abiotic nature of the Tatra Mountains: A new cartographic picture - Kotarba, Adam (IGiPZ PAN, 2016)
The Atlas of the Tatra Mountains is published by the Tatra National Park. This excellent work was elaborated by a team of 130 scientists from Poland and Slovakia. Abiotic nature in these mountains is depicted on 82 maps and 165 accompanying illustrations. The maps illustrate both the Polish and Slovak parts of the Tatras, and contain explanations in three languages: Polish, Slovak and English.
24 cm
Keywords: physico-geographic regions; climate; waters; geological setting and underground waters; relief; soils and types of natural environment; Poland; Slovakia; Tatra Mountains